Real‐world effectiveness of guselkumab in patients with psoriasis: Health‐related quality of life and efficacy data from the noninterventional, prospective, German multicenter PERSIST trial. Issue 12 (12th September 2021) - Gerdes, Sascha; Bräu, Beate; Hoffmann, Matthias; Korge, Bernhard; Mortazawi, Dariusch; Wiemers, Franca; Wegner, Sven; Personke, Yvonne; Gomez, Mario; Sticherling, Michael
Abstract: Psoriasis is a common, chronic inflammatory skin disorder negatively impacting health‐related quality of life (HRQoL). Guselkumab, targeting interleukin‐23 (IL‐23), is an approved biologic therapy for psoriasis. PERSIST is an ongoing prospective, noninterventional, long‐term, German multicenter study evaluating the effect of guselkumab on HRQoL, and its efficacy and safety in patients with moderate‐to‐severe psoriasis in a real‐world setting. The primary endpoint is the proportion of patients with a Dermatology Life Quality Index (DLQI) score ≤ 1 at week 28. Of 303 patients enrolled and treated with guselkumab, mean age and disease duration were 49.7 and 21.0 years, respectively, and 51.2% ( n = 155) of patients had received ≥1 prior biologic therapy. Mean baseline DLQI score was 13.7, and mean symptom and sign scores in the Psoriasis Symptoms and Signs Diary (PSSD) were 51.9 and 60.8, respectively. Baseline Psoriasis Area Severity Index (PASI) and body surface area (%) scores were 16.4 and 27.5. Following 28 weeks of guselkumab treatment, the mean DLQI score decreased to 2.8, and 56.8% of patients ( n = 150) achieved DLQI ≤ 1. Mean PSSD symptom and sign scores also improved, decreasing to 12.5 and 15.9, respectively. At week 28, PASI 90 response was 55.3%; significant improvement was observed in patients with psoriasis in difficult‐to‐treat areas. Overall, analyses demonstrated that guselkumab was effective in the real‐world setting, as measured by HRQoL and skin improvements, even in patients with a high burden of disease and those who have received multiple biologic therapies. No new safety signals were observed.